Ferramenta metodológica de gestão para a avaliação das áreas de preservação permanente de Recursos Hídricos urbanos. - Vasconcelos, Francisca Dalila Menezes (2021)
The claim that the Permanent Preservation Areas (APP) of water resources are directly affected by urban expansion is widely accepted. Considering that, in Brazil, water resources belong to the Union or to States, including urban rivers, it is concluded that there are no water resources in the municipal domain; however, it is up to the municipality to organize, use and occupy the land, especially the PPAs. Thus, the legal inconsistency and the fragmentation of competences on the management of urban water resources - which lies in the conflict over applying the Brazilian Forest Code (CFB) or the Municipal Master Plan (PDM) to areas of permanent preservation - promotes the vulnerability of rivers in the face of urban expansion. Exposed to the problem, the present work proposes a management tool to assess the quality of water resource APPs in the face of the urban expansion process, as these areas perform essential functions in the urban context. The tool was applied to the city of Fortaleza, Ceará, and consists of three stages: i) definition of a strategy for delimiting APPs; ii) proposition and application of the APPHidro composite index and iii) application of the prospective scenario over a ten-year horizon to understand the possible impacts and their future consequences. The proposed strategy for the delimitation of APPs resulted in seven profiles of these areas, total quantitative of the areas of water resources, preserved and occupied APPs. The APPHidro index presents the result 22.32 on a scale from 0 to 100 (the closer to 100 the higher the quality of the APP), configuring the “Inefficient management of the APPs”, revealing that recovery measures are necessary to be applied in these areas. In the prospective scenario, the first scenario follows the trend based on past events; the second comprises the actions of strategic planning and complies with the Brazilian Forest Code; and the third scenario adopts technological innovations and restructuring of the current management and environmental legislation. The results present an overview of the APPs, allow the monitoring of areas and generate accessible and easy-to-understand information. Based on the prospective scenarios built, guidelines and strategies available to decision makers are presented, which aim to guarantee the ecosystem services performed by urban springs, in addition to presenting strategies for sustainable ordering in the occupation of APPs.